Удосконалення шляхів взаємодії залізниці та клієнта в сучасних ринкових умовах - Стрелко, Олег; Бердниченко, Юлія; Щербина, Розалія (ТзОВ «Галицька видавнича спілка», 2021)
The need to create a quality service system for cargo owners is due to the reformation of Ukraine’s rail transport. This is achieved by the most complete satisfaction of customers' requirements for the quality of transportations and related services.
Improving the ways of interaction between the railway and the customer in modern market conditions
Keywords: 656.2